This is a love story : a novel - Soffer, Jessica (New York : Dutton, 2025)
For fifty years, Abe and Jane's love unfolded in Central Park. Now, as Jane is dying, Abe recalls their life together. Through shifting perspectives$1 (Bincluding the Park's$1 (Bthis poignant story captures the complexity, endurance, and beauty of love across time.s
Keywords: Older people -- Fiction; Terminally ill -- Fiction; Marriage -- Fiction; Reminiscing in old age -- Fiction; Artists -- Fiction; Families -- Fiction; Central Park (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Romance fiction